Analysis and discussion on the pharmaceutical centralized procurement implementation — a case study of a large provincial hospital in China - Cao, Jingjing; Ren, Yuan; Zhao, Chenglong; Wang, Li; Fang, Fengqin (Frontiers in Pharmacology, 2024)
Unaffordable medical treatment and inflated drug prices have become a challenging issue for lawmakers worldwide. To reduce the financial burden and standardize the pharmaceutical market, the Chinese government has issued several detailed regulations, including the measures of drug recruitment and procurement in one and volume purchasing to not only ensure the high quality of approved drugs but also lower the cost of the production and sell procedure. In this work, to have a thorough overview of the enforcement of these regulations, we attempted to critically analyze the data of our hospital's centralized procurement of drugs from 2019 to 2022.We identified some concerns, such as the difficulty in determining the "quantity" of drug procurement, out-of-stock of collectively procured drugs, difficulty in managing the preallocation of associated funds, incomplete centralized procurement systems, etc. Therefore, it is essential to promote a multidimensional strategy, including the combination of the medical insurance reform and drug centralized procurement policies, strict controlling of the forecast quantity of drugs to ensure stable drug supply, improvement of the relevant policies for retaining the surplus of centralized procurement drug medical insurance funds, secureness of the drug procurement system platform, and available reference and guidance for subsequent centralized quantity procurement of drugs.Keywords Pharmaceutical Centralized purchase, quantity of centralized procurement tasks, rules of centralized procurement, drug supply, repaymentState-organized centralized procuring of medicines with quantity, also referred to as "national centralized procurement" or "procuring with quantity", involves the state selecting generic medicines varieties that have passed the consistency evaluation for quality and efficacy, and concentrating the scattered purchasing volume of medical institutions nationwide into a